MEDIA RADIO SEBAGAI PUBLIC SPHERE DALAM PEMBENTUKAN OPINI PUBLIK - Tita Melia Milyane (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
This paper describes the phenomenon of radio in Indonesia is experiencing a revival since the collapse of the new order and the emergence of democratic society and freedom of opinion and freedom of the press. However, of the approximately 948 radio in Indonesia which consists of 750 licensed commercial radio , radio 146 which is managed by the government and 52 radio station RRI , only about 35 radio stations are broadcasting organizes public opinion or provide a public space for the listener. Yet radio has the power as a specialized mass media , have raised the character of local knowledge , including the various problems in society that are local.